PMO-059 Parenteral nutrition: audit of usage in a district general hospital without a nutrition support team. (28th May 2012) - Phillips, A; Brown, J; Hinton, K; Gee, I
Abstract : Introduction: Parenteral nutrition (PN) is well known to have possibility of serious sequelae, in particular from catheter related sepsis (CRS). Multiple studies have demonstrated that a Nutrition Support Team (NST), in particular a Nutrition Support Nurse (NSN), can reduce inappropriate PN as well as reducing CRS rates (Kennedy et al 2005). The aim of this audit was to document PN usage in a district general hospital without a NST or NSN. Methods: All patients in whom PN was initiated in 2010 at Worcester Royal Hospital were assessed retrospectively by case note review by a single author (AMP). A list of all patients who had received PN was kept by the Pharmacy department, ensuring a 100% pick up rate. Appropriate PN indications were defined according to the NICE guidelines. Patients with a functional and usable GI tract (capable to absorb adequate nutrients via appropriate enteral tube access), patients in whom dependence on PN was anticipated to be <5 days and patients whose prognosis did not warrant aggressive nutritional support were defined as receiving inappropriate PN. CRS was judged to have occurred when the patient had a temperature of ≥38.0°C along with either a subsequent positive line tip culture or positive blood cultures in the absence of any other potential source of sepsis. Results: 61.4% of the patients were male. The median age at commencement of PN was 67.1 (IQR 59.9–80.3). There were 101 episodes of PN, with a median duration of PN of 7 days (IQR 5–14). A total of 1214 days of PN were administered. Full information was available for 92 of these episodes, a total of 1093 days. The majority of PN was given via non-tunnelled central venous catheters (58.3%) with a further 23.7% by Hickmann line, and 13.4% peripherally. Sixty-eight of the episodes were assessed to have been initiated for appropriate indications: 50% of these due to ileus, 19.1% due to obstruction and 14.7% due to fistulae. Twenty-four episodes, totalling 182 days of PN, were judged to have been inappropriate, predominantly due to inadequate consideration being given to enteral tube access. CRS complicated 16 of the episodes (17.4%) and there were 18 CRS events, equating to 16.5 events/1000 catheter days. The majority of these (16/18) were due to coagulase negative S aureus . Conclusion: Inappropriate PN and CRS rates are at the level that would be expected in a hospital where there is no NST. Increased vetting of PN referrals and more effective training in line care that would come with a formal NST could have cost benefits for the trust. Competing interests: None declared.